Use of technology and document management systems for SOPs - Turner, Gareth (Henry Stewart Talks, 2013)
Using technology or EDMS for SOPs, The place of paper and of technology, A basic EDMS, What to expect from your EDMS, Meta data, Document versioning, publishing & security, Collaborative creation, Work flow, Electronic signatures, Linking documents, Guidance for associated documents, Forms & templates, Using a bridging document, Thoughts for the future